Potential Application of Perovskite Structure for Water Treatment: Effects of Band Gap, Band Edges, and Lifetime of Charge Carrier for Photocatalysis - Clabel H., J. L.; Chacaliaza-Ricaldi, J.; Marega Jr, E. (Frontiers in Nanotechnology, 2022)
Perovskite structures have attracted scientific interest as a promising alternative for water treatment due to their unique structural, high oxidation activity, electronic stability, and optical properties. Besides, the photocatalytic activity of perovskite structures is higher than that of many transition metals compounds. A critical property that determines the high-performance photocatalytic and optical properties is the band gap and lifetime of carrier charge. Thus, the synthesis/processing and study of effect band gap and lifetime of carrier charge in the development of high-performance photocatalysts for water treatment are critical. This review presents the basic physical principles of optical bandgaps, their bandgap tunability, potentials and limitations in the applications for the water treatment. Furthermore, it reports recent advances in the synthesis process and comparatively examines the effect band gap in the response photocatalytic. In addition to the synthesis, the physical mechanisms associated with the change in the band gap have been discussed. Finally, the conclusions of this review, along with the current challenges of perovskites for photocatalysis, are presented.